Education and "human capitalists" in a classical-Marxian model of growth and distribution - Amitava Krishna Dutt; Roberto Veneziani (Queen Mary University of London, School of Economics and Finance, 2017)
A simple classical-Marxian model of growth and distribution is developed in which education transforms low-skilled workers into high-skilled ones and in which high-skilled workers save and hold capital, therefore receiving both high-skilled wages and profit income. We analyze the implications for class divisions, growth and distribution, of the transformation of the modern capitalist economy from one in which the main class division is between capitalists who own capital and workers who only receive wage income into one in which education and human capital play a major role. We show than an expansion in education can have a positive effect on growth but by altering the distribution of income rather than by fostering technological change, and that it yields some changes in income distribution and the class structure of the capitalist economy, but need not alter its fundamental features.
Keywords: E2; E11; O41; I24; 330; Education; Human capital; Workers' savings; Growth; Distribution